The analysis of the Contest of Competence No. 18-2004. Interpretation and application of the law under the Constitution and the American Convention on Human Rights - Castañeda Otsu, Susana Ynés (2020)
The present article analyzes and interprets the Litigation of Competition relapse in the N° 18-2004 File, explaining its ends withnormative character, referred to the reaches of the military jurisdiction and the notion of function of the members of the Armed Forces and the National Police of Peru